2017
DOI: 10.1016/j.jvs.2017.01.053
|View full text |Cite
|
Sign up to set email alerts
|

The association of postoperative glycemic control and lower extremity procedure outcomes

Abstract: One in five patients undergoing vascular procedures had postoperative hyperglycemia. Postoperative hyperglycemia was associated with adverse events after lower extremity vascular procedures in patients with and without diabetes, including infection, increased hospital utilization, and mortality. No difference was found with respect to hospital readmission. Postprocedure glucose management may represent an important quality marker for improving outcomes after lower extremity vascular procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 26 publications
(29 reference statements)
1
22
0
1
Order By: Relevance
“…Patients who were hyperglycemic post-operatively manifested a higher rate of infection, increased hospital utilization and in-hospital mortality. 16 In a similar manner to other large database studies in colorectal and gastrointestinal surgery, we found that post-operative complications during the index hospitalization were linked to increased utilization of healthcare resources and an increased readmission rate. 18,19 As has been described in other large patient series, any complication during the index hospitalization predisposes to an increased risk of readmission.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Patients who were hyperglycemic post-operatively manifested a higher rate of infection, increased hospital utilization and in-hospital mortality. 16 In a similar manner to other large database studies in colorectal and gastrointestinal surgery, we found that post-operative complications during the index hospitalization were linked to increased utilization of healthcare resources and an increased readmission rate. 18,19 As has been described in other large patient series, any complication during the index hospitalization predisposes to an increased risk of readmission.…”
Section: Discussionsupporting
confidence: 82%
“…Infectious complications in vascular surgery patients has also been studied in large health care databases. 15,16 An analysis using Health Facts evaluated 3,586 patients undergoing lower extremity vascular procedures. Patients who were hyperglycemic post-operatively manifested a higher rate of infection, increased hospital utilization and in-hospital mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they highlight an unmet need to delineated independent risk factors of POHG and its associated complications Among patients being cared for in surgical units, the incidence of POHG is quite high, depending on the attributes of the institution and its catchment area, the nature of the illnesses being treated, patient comorbidities and the specific classes of surgical procedures. The incidence of POHG, ranges from 22 % in vascular surgeries [10] to 77% in cardiac surgeries [11] and from 16% in nondiabetics [12] to 24% in diabetics [13]. Perioperative and intensive care unit blood glucose control and management without major glycemic variation have been shown to improve outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is associated with several adverse outcomes and complications including higher mortality, sepsis, surgical site infection, pneumonia, and prolonged hospitalization. [2,10] The incidence of stress hyperglycemia is more likely in patients with a preoperative diagnosis of type 2 diabetes (T2D) and impaired glucose metabolism and control. [3] Strikingly, POHG has been observed among patients who are not known to have T2D.…”
Section: Introductionmentioning
confidence: 99%
“…Among patients being cared for in surgical units, the incidence of POHG is quite high, depending on the attributes of the institution and its catchment area, the nature of the illnesses being treated, patient comorbidities and the speci c classes of surgical procedures. The incidence of POHG, ranges from 22 % in vascular surgeries [10] to 77% in cardiac surgeries [11] and from 16% in non-diabetics [12] to 24% in diabetics [13]. Perioperative and intensive care unit blood glucose control and management without major glycemic variation have been shown to improve outcomes.…”
Section: Introductionmentioning
confidence: 99%